The effect of plyometric exercise on bone mineralisation and physical fitness in adolescents - Syahrul Syahrul; Rijal Rijal; Yudi Hardianto; Rabia Rabia (Physiotherapy Quarterly)
Introduction Plyometric exercise is the preferred type of exercise to promote bone health due to its role on providing high-impact loading of bone tissue. This study aimed to evaluate the effect of plyometric training on bone mineralisation and physical fitness between male and female adolescents.